Acute myeloid leukemia relapse after allogeneic hematopoietic stem cell transplantation: a retrospective study from a single institution. Issue 2 (February 2022) - Lin, Cheng-Hsien; Chen, Tsung-Chih; Shih, Yu-Hsuan; Chou, Cheng-Wei; Hsu, Chiann-Yi; Li, Po-Hsien; Teng, Chieh-Lin Jerry
Objective: The outcomes of patients with acute myeloid leukemia (AML) who relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) are poor. However, the risk factors for relapse in this context remain unclear. Methods: We retrospectively assessed 84 consecutive adult AML patients who underwent allo-HSCT and achieved complete remission (CR). These patients were dichotomized into non-relapse (n = 58) and relapse (n = 26) groups, and the cumulative relapse rates and associated risk factors were examined. We also examined the treatments for and outcomes of patients with AML relapse after allo-HSCT. Results: Non-CR status before allo-HSCT and high-risk cytogenetics were significant risk factors for AML relapse in univariate analysis, and non-CR status was also identified as a risk factor in multivariate analysis. The cumulative AML relapse rates after allo-HSCT were significantly higher in patients with non-CR (70.0%) compared with patients with CR (25.6%). Only 2 of the 26 relapsed patients remained alive on the study-censored day. Conclusions: Non-CR status before allo-HSCT was a significant risk factor for AML relapse after allo-HSCT. Patients with AML relapse after allo-HSCT had poor outcomes due to a lack of response to salvage remission-induction chemotherapy or treatment-related adverse events.